PENGARUH INSENTIF TERHADAP KINERJA MELALUI KECERDASAN EMOSIONAL - Sinaga, Elvrida Novianna; Absah, Yeni; Rini, Endang Sulistiya (Jurnal Muara Pendidikan, 2024)
This research aims to find out the influence of Incentives on Performance through the Emotional Distress of Teachers of SMAN 1 Matauli.  This associative research with a quantitative analysis approach using primary data and secondary data. The data analysis methods used are descriptive statistical analysis, path analysis, and path diagrams. The population in this study were all teachers of SMAN 1 Matauli, totaling 69 teachers. The sample in this research totaled 69 respondents. The research show that Incentives have a positive and significant effect on Performance, Incentives have a negative and insignificant effect on Emotional Intelligence, Emotional Intelligence has a positive and insignificant effect on Performance, Emotional Intelligence is unable to mediate the relationship between Incentives and Teacher Performance at SMAN 1 Matauli.